5. EVALUATION OF LEADERSHIP POLICY OF DEAN IN EFFORTS TO INCREASE READY-TO-USE GRADUATES (STUDY PROGRAM OF STUDENT CREATIVITY ANIMAL HUSBANDRY FACULTY OF BRAWIJYA UNIVERSITY) - Malang, Sekolah Tinggi Ilmu Administrasi (STIA) (STIA Malang, 2019)
AbstractThis study uses qualitative research aims to observe, to know, to observe socialphenomena in a setting, as well as developing the concept in solving a problem,the data were collected by interview (a responsibility), supported by resourcepersons as needed research. Data analysis using interactive analysis model ofMiles and Huberman that consists of data collection, the data display, datareduction and Conclusions; drawing/verifying policies to improve the quality ofcollege graduates to someday have the academic ability to develop, apply anddisseminate knowledge, technology and creativity in the field of animalhusbandry. Still, rare students who are interested and are interested in theprogram of student creativity. not a few who do not or do not want to take anychance that the CRP program, perhaps because students have not found meaningor benefit from the program, or students feel less time to learn, assumed to followsuch activities are a waste of time. students can also just want to focus onactivities in order to achieve IP college or high GPA. if such a fact, then there isa lot of students to be students butterfly (college tuition home- return). therefore,for the students, while in college is an opportunity to develop themselves, then tryto take the opportunity offered by CRP. proved to be quite a lot of graduates whocan compete in the world of work, to create jobs that are received at theenterprise, government, and private agencies as actively participating in theCRP program.Keyword: leadership policy, graduates student, animal husbandry faculty